Exo70 intracellular redistribution after repeated mild traumatic brain injury - Lira, Matías; Zamorano, Pedro; Cerpa, Waldo (My University, 2021)
Abstract Background: Exo70 is a subunit of the greater exocyst complex, a collection of proteins that oversees cellular membrane addition and polarized exocytosis by acting as a tethering intermediate between the plasma membrane and newly synthesized secretory vesicles. Although Exo70 function has been implicated in several developmental events including cytokinesis and the establishment of cell polarity, its role in neuropathologies is poorly understood. On the other hand, traumatic brain injury is the result of mechanical external force including contusion, fast acceleration, and expansive waves that produce temporal or permanent cognitive damage and triggers physical and psychosocial alterations including headache, memory problems, attention deficits, difficulty thinking, mood swings, and frustration. Traumatic brain injury is a critical health problem on a global scale, constituting a major cause of deaths and disability among young adults. Trauma-related cellular damage includes redistribution of N-methyl-D-aspartate receptors outside of the synaptic compartment triggering detrimental effects to neurons. The exocyst has been related to glutamate receptor constitutive trafficking/delivery towards synapse as well. This work examines whether the exocyst complex subunit Exo70 participates in traumatic brain injury and if it is redistributed among subcellular compartments Results: Our analysis shows that Exo70 expression is not altered upon injury induction. By using subcellular fractionation, we determined that Exo70 is redistributed from microsomes fraction into the synaptic compartment after brain trauma. In the synaptic compartment, we also show that the exocyst complex assembly and its interaction with GluN2B are increased. Finally, we show that the Exo70 pool that is redistributed comes from the plasma membrane. Conclusions: The present findings position Exo70 in the group of proteins that could modulate GluN2B synaptic availability in acute neuropathology like a traumatic brain injury. By acting as a nucleator factor, Exo70 is capable of redirecting the ensembled complex into the synapse. We suggest that this redistribution is part of a compensatory mechanism by which Exo70 is able to maintain GluN2B partially on synapses. Hence, reducing the detrimental effects associated with TBI pathophysiology.
Keywords: hippocampus; exocyst; exo70; compartmentalization; redistribution; traumatic brain injury